Representasi Eksploitasi Kemiskinan Pada Program “Orang Pinggiran” (Episode Sepenggal Kisah Anak Gembala di Trans 7) - Rizky An Nahl; Rifma Ghulam; Abdul Khohar (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The program "Orang Pinggiran" portrays the lives of marginalized communities in Indonesia, with one of its episodes, "Sepenggal Kisah Anak Gembala," depicting the struggles of Juriyah's family. This study aims to analyze the representation of poverty in this episode using Roland Barthes' semiotic approach, which distinguishes between denotative and connotative meanings. The research method involves semiotic analysis, evaluating visual and narrative signs to reveal deeper meanings. The findings show that the program not only represents the physical conditions of poverty but also constructs a narrative that reinforces connotative meanings related to resilience and hope in the face of adversity. In conclusion, the episode effectively uses signs to illustrate the complex social realities, inviting viewers to reflect on issues of injustice and resilience amidst poverty.